Meningkatkan Kualitas Pembelajaran Pendidikan Agama Kristen Melalui Model Team Game Tournament - Alisaba Lombu (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This research was conducted at SD Negeri Tuhegeo II Gununungsitoli Idanoi and this research was carried out with a Classroom Action Research (CAR) approach. Based on the results of research and discussion, after being evaluated and analyzed it can be concluded that the use of cooperative learning model team game tournament (TGT) method in learning Christian Religious Education can optimally improve the quality of Christian Religious Education learning for grade VI SD Negeri Tuhegeo II Gununungsitoli Idanoi. This can be seen from the success rate of every aspect of the quality of the process and learning outcomes which have increased in cycle II and have met or exceeded each of the expected targets. The increase in the quality of learning outcomes is indicated by the class average score which was originally obtained in the initial ability test only obtained an average value of 58.42 in the first cycle increased to 63.85 and in the second cycle increased again to 70.42. In the initial ability test, students who could reach the complete limit were only 55.3%, while in the first cycle it increased to 62.2% and in the second cycle it reached 80.6%, which means that they have reached the minimum completeness criteria of school and the national level of 75%. Keywords: Quality of Learning; Team Game Tournament    Abstrak: Penelitian ini dilaksanakan di SD Negeri Tuhegeo II Gununungsitoli  Idanoi dan Penelitian ini dilaksanakan dengan pendekatan Penelitian Tindakan Kelas (PTK) Berdasarkan hasil penelitian dan pembahasan, setelah dievaluasi dan dianalisis dapat disimpulkan bahwa penggunaan model pembelajaran kooperatif metode team game tournament (TGT) pada pembelajaran Pendidikan Agama Kristen secara optimal dapat meningkatkan kualitas pembelajaran Pendidikan Agama Kristen siswa Kelas VI SD Negeri Tuhegeo II Gununungsitoli Idanoi . Hal ini terlihat dari tingkat keberhasilan setiap aspek kualitas proses dan hasil pembelajaran yang mengalami peningkatan pada siklus II dan telah memenuhi bahkan melebihi masing-masing target yang diharapkan. Peningkatan kualitas hasil belajar ditunjukkan dengan nilai rata-rata kelas yang semula pada tes kemampuan awal hanya diperoleh nilai rata-rata sebesar 58,42 pada siklus I meningkat menjadi 63,85 dan pada siklus II meningkat lagi menjadi 70,42. Pada tes kemampuan awal siswa yang dapat mencapai batas tuntas hanya 55,3%, sedangkan pada siklus I meningkat menjadi 62,2 % dan pada siklus II mencapai  80,6  %  yang  berarti  sudah  mencapai  kriteria  ketuntasan  minimal sekolah dan nasional sebesar 75%. Kata Kunci: kualitas pembelajaran; Team Game Tournament